PSVII-13 Effects of corn supplementation on muscle microRNA profiles within horses. (5th December 2019) - Carver, Clarissa M; Hess, Tanja; Bruemmer, Jason; Coleman, Stephen; Landolt, Gabriele
Abstract: The objective of this study was to determine the effect of corn supplementation on muscle microRNA (miRNA) profiles. Twelve mares were blocked by weight and BCS and assigned to one of two treatments (6 hd/treatment): 1) control, (basal diet: 9 Kg/hd/d of chopped mixed grass hay and ad libitum mixed grass hay), 2) basal diet supplemented with 454 g/d steam flaked corn individually using feed bags. All mares were placed on the basal diet and in the same pen 14 days prior to the beginning of corn supplementation. Mares were weighed and BCS on d -7 and 28. Muscle biopsies of the gluteus medius were taken from all horses on d0 and d26. Muscle samples were analyzed using real time RT-qPCR for 277 endogenous miRNAs. Raw CT values were normalized with the geometric mean of three consistently appearing endogenous miRNAs. Sixteen miRNAs that consistently appeared in at least 8 horses including 3 relating to metabolic disorders appearing at d0, d26, or both were analyzed. Differential abundances of miRNAs using log transformed fold change and differences between BW and BCS of treatment groups were determined by ANOVA and LS means analysis. There was no difference between BW (P < .05) and BCS (P < .05) between the two treatment groups. Feeding corn lead to higher quantities (P < .05) of mir 133a, 1515p, 6155p, 770, and 99b within muscle compared to control group. Lower quantities of mir 382 and 433 were found within muscle of horses fed corn compared to the control group (P < .05). Based upon the results of this study corn supplementation appears to influence endogenous miRNA expression profiles within muscle of horses.